Дослідження соціально-економічних аспектів збитковості внаслідок поширення депресивних розладів - Яковлева, Ольга Станіславівна; Yakovleva, O. S. (Х. : НФаУ, 2018)
З метою фармакоекономічно обґрунтованого підходу до вибору лікарських засобів проаналізовано епідеміологічні показники, медико-соціальні та економічні наслідки поширення депресивних розладів. За результатами встановлено, що депресивні розлади є важливою соціально-економічною проблемою у всіх країнах світу. За останній час спостерігається зростання економічного тягаря депресивних розладів, який обумовлений, не стільки з фінансовим забезпеченням діагностики і лікування даних розладів, скільки з непрямими витратами: трудовими втратами, забезпеченням різноманітних форм соціальної підтримки, зайнятістю членів сім'ї турботами про хворих та інш. Важливого значення набуває вибір медичної технології, яка сприятиме соціальному функціонуванню хворих на депресивні розлади та скороченню непрямих витрат. Epidemiological indicators, medical and social and economic consequences of the depressive disorders’ spread are analyzed in order to make a well-founded choice of the pharmacoeconomic method of the drug analysis. It is established according to the results, that depression is an important socio-economic problem in all countries of the world. Recently, there has been an increase in the economic burden of the depressive disorders, which is caused not only with financial support of the diagnostics and the treatment of these disorders, but with indirect costs: labor losses, the provision of various forms of social support, the employment of family members caring for the patients and others. Therefore, an important task is to ensure the availability of medical and pharmaceutical care of the patients. At the same time carrying out the pharmacoeconomic researches should be directed on the reasonable choice of medical technology, which provides treatment, social functioning of the patients and reduction of indirect costs.
Research of social economic aspects of unprofitableness as a result of depressive disorders’ distribution